Abundance-based distribution modelling reveals climate-driven loss of functionally important kelp forest habitat - Patrick Eskuche-Keith; Heather E. Sugden; Michael T. Burrows; Pippa J. Moore; Clare Fitzsimmons; Dan A. Smale; Benjamin Hall; Fabrice Stephenson (Journal of Environmental Management, 2026)

Person-level health factors partially mediate the association between lesbian, gay, or bisexual (LGB) identity, allostatic load, and cancer mortality in NHANES - Justin Xavier Moore; Alisha Patel; Missy Spears; Tracy Casanova; Heidi L. Weiss; Marvin E. Langston; Keith J. Watts; Donte Boyd; Prajakta Adsul; Meredith Duncan; Sydney Howard (Cancer Causes & Control, 2026)

Necessity for modeling hormonal crosstalk in arabidopsis root development? - Simon Moore; Junli Liu; Chunli Chen; Keith Lindsey (Trends in Plant Science, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Century‐scale loss and change in the fishes and fisheries of a temperate marine ecosystem revealed by qualitative historical sources - Alec B. M. Moore; Keith Brander; Shaun Evans; Poul Holm; Jan Geert Hiddink (Fish and Fisheries, 2024)
Policies aiming to restore ecosystems, achieve thriving fisheries and reverse biodiversity loss require knowledge of their former status and long‐term variation. As quantitative fish data is typically only available for recent decades long after changes may have occurred, a greater use of qualitative sources has been encouraged in marine historical ecology. We examined diverse historical information (including maritime history, fisheries reports, naturalists' accounts, recipes, nautical charts and newspapers) across a multi‐century time span (13th–20th century) for a wide range of species to document their long‐term trajectories in an understudied Northeast Atlantic ecosystem (Irish Sea coast of Wales). We find strong evidence of the loss of both a pelagic fishery for herring, which was of fundamental socio‐ecological importance since at least the 13th century, and the loss of significant multi‐species demersal and intertidal fisheries. Local, commercial and/or functional extinction has occurred for taxa spanning a wide range of diversity (crustacean, elasmobranchs, sturgeon, and teleosts), body size and ecological role, suggesting far‐reaching changes to food webs. This raises fundamental questions about the present‐day health and integrity of this coastal ecosystem and the long‐term viability of current fisheries which depend on a few shellfish species. Our century‐scale synthesis of qualitative data for multiple taxa allows the collective breadth of losses to be fully appreciated and may reduce the risk of ‘shifting baselines’. Restoration to historical baselines may not be achievable, but our findings provide evidence of long‐term change relevant to policies for recovery, and prevention of further decline of fishes, fisheries and ecosystems.

Planning and licensing for marine aquaculture - Lynne Falconer; Karl Cutajar; Amalia Krupandan; Elisa Capuzzo; Richard A. Corner; Tim Ellis; Keith Jeffery; Eirik Mikkelsen; Heather Moore; Francis X. O'Beirn; Pauline O'Donohoe; Neil M. Ruane; et al. (Reviews in Aquaculture, 2023)
Marine aquaculture has the potential to increase its contribution to the global food system and provide valuable ecosystem services, but appropriate planning, licensing and regulation systems must be in place to enable sustainable development. At present, approaches vary considerably throughout the world, and several national and regional investigations have highlighted the need for reforms if marine aquaculture is to fulfil its potential. This article aims to map and evaluate the challenges of planning and licensing for growth of sustainable marine aquaculture. Despite the range of species, production systems and circumstances, this study found a number of common themes in the literature; complicated and fragmented approaches to planning and licensing, property rights and the licence to operate, competition for space and marine spatial planning, emerging species and diversifying marine aquaculture production (seaweed production, Integrated Multi‐Trophic Aquaculture [IMTA], nutrient and carbon offsetting with aquaculture, offshore aquaculture and co‐location and multiuse platforms), and the need to address knowledge gaps and use of decision‐support tools. Planning and licensing can be highly complicated, so the UK is used as a case study to show more detailed examples that highlight the range of challenges and uncertainty that industry, regulators and policymakers face across interacting jurisdictions. There are many complexities, but this study shows that many countries have undergone, or are undergoing, similar challenges, suggesting that lessons can be learned by sharing knowledge and experiences, even across different species and production systems, rather than having a more insular focus.

Verification and benchmarking relativistic electron beam transport through a background gas - Brandon M. Medina; Pierre Grua; Keith L. Cartwright; David Hébert; Nicolas Szalek; Clément Caizergues; Israel Owens; Elaine L. Rhoades; Jacques Gardelle; Christopher H. Moore (Computer Physics Communications, 2023)

Biomass Quality Responses to Selection for Increased Biomass Yield in Perennial Energy Grasses - Michael D. Casler; DoKyoung Lee; Robert B. Mitchell; Kenneth J. Moore; Paul R. Adler; R. Mark Sulc; Keith D. Johnson; Robert L. Kallenbach; Arvid R. Boe; Russell D. Mathison; Kim A. Cassida; Doohong Min; et al. (BioEnergy Research, 2023)

Response of nitrate leaching to no‐tillage is dependent on soil, climate, and management factors: A global meta‐analysis - Jinbo Li; Wei Hu; Henry Wai Chau; Mike Beare; Rogerio Cichota; Edmar Teixeira; Tom Moore; Hong Di; Keith Cameron; Jing Guo; Lingying Xu (Global Change Biology, 2023)
No tillage (NT) has been proposed as a practice to reduce the adverse effects of tillage on contaminant (e.g., sediment and nutrient) losses to waterways. Nonetheless, previous reports on impacts of NT on nitrate () leaching are inconsistent. A global meta‐analysis was conducted to test the hypothesis that the response of leaching under NT, relative to tillage, is associated with tillage type (inversion vs non‐inversion tillage), soil properties (e.g., soil organic carbon [SOC]), climate factors (i.e., water input), and management practices (e.g., NT duration and nitrogen fertilizer inputs). Overall, compared with all forms of tillage combined, NT had 4% and 14% greater area‐scaled and yield‐scaled leaching losses, respectively. The leaching under NT tended to be 7% greater than that of inversion tillage but comparable to non‐inversion tillage. Greater leaching under NT, compared with inversion tillage, was most evident under short‐duration NT ( −1 ), in medium texture and low SOC ( 200 kg ha −1 ) and lower (0–100 kg ha −1 ) rates of nitrogen addition. Of these, SOC was the most important factor affecting the risk of NO 3 − leaching under NT compared with inversion tillage. Globally, on average, the greater amount of NO 3 − leached under NT, compared with inversion tillage, was mainly attributed to corresponding increases in drainage. The percentage of global cropping land with lower risk of NO 3 − leaching under NT, relative to inversion tillage, increased with NT duration from 3 years (31%) to 15 years (54%). This study highlighted that the benefits of NT adoption for mitigating leaching are most likely in long‐term NT cropping systems on high‐SOC soils.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Climatic and landscape changes as drivers of environmental feedback that influence rainfall frequency in the United States - Rachel A. Moore; Davide Martinetti; E. Keith Bigg; Brent C. Christner; Cindy E. Morris (Global Change Biology, 2021)
Previous studies have identified regions where the occurrence of rainfall significantly increases or decreases the probability for subsequent rainfall over periods that range from a few days to several weeks. These observable phenomena are termed “rainfall feedback” (RF). To better understand the land–atmosphere interactions involved in RF, the behavior of RF patterns was analyzed using data from 1849 to 2016 at ~3000 sites in the contiguous United States. We also considered changes in major land‐use types and applied a geographically weighted regression model technique for analyzing the predictors of RF. This approach identified non‐linear and spatially non‐stationary relationships between RF, climate, land use, and land type. RF patterns in certain regions of the United States are predictable by modeling variables associated with climate, season, and land use. The model outputs also demonstrate the extent to which the effect of precipitation, temperature, and land use on RF depend on season and location. Specifically, major changes were observed for land use associated with agriculture in the western United States, which had negative and positive influences on RF in summer and winter, respectively. In contrast, developed land in the eastern United States correlated with positive RF values in summer but with negative ones in winter. We discuss how changes in climate and land use would be expected to affect land–atmosphere interactions, as well as the possible role that physical mechanisms and rain‐enhanced bioaerosol emissions may play in the spatiotemporal changes observed for historical patterns of rainfall frequency in the United States.

Potential competition between marine heterotrophic prokaryotes and autotrophic picoplankton for nitrogen substrates - Wenchao Deng; Shanlin Wang; Xianhui Wan; Zhenzhen Zheng; Nianzhi Jiao; Shuh‐Ji Kao; Jefferson Keith Moore; Yao Zhang (Limnology and Oceanography, 2021)
Heterotrophic prokaryotes have the capacity to uptake inorganic nitrogen (N) substrates. However, it remains unclear what the potential competition is between heterotrophic prokaryotes and autotrophic plankton for N in the ocean, which would shunt the flow of N supporting primary production. To date, it has been difficult to distinguish heterotrophic prokaryotic N uptake from that of autotrophic picoplankton, especially in oligotrophic oceans dominated by cyanobacteria. We carried out field‐based DNA stable isotope probing incubation experiments in the South China Sea combining measurements of uptake rates of ammonium, nitrate, nitrite, and urea to estimate the taxon‐specific potential N assimilation. The results indicate that phylogenetically diverse heterotrophic prokaryotes significantly incorporated multiple N sources, contributing approximately 17–41% and 19–55% of total N uptake potential in the euphotic zone of the South China Sea continental shelf and open ocean, respectively, potentially competing with cyanobacteria (mainly Prochlorococcus ). Notably, heterotrophic prokaryotes made a higher contribution to bulk uptake of nitrate in the incubation systems of the open ocean relative to regenerated N, and thus there was a tendency to overestimate the f ‐ratio. Extrapolating our results to the oligotrophic, low‐latitude ocean via a global model suggests the f ‐ratio would decrease ~ 18%. This suggests a more complicated biogeochemical role of heterotrophic prokaryotes in the biological carbon pump than hitherto assumed, with important implications for N and carbon cycling in the vast open ocean.

Save Our Species: A Blueprint for Restoring Butternut ( Juglans cinerea ) across Eastern North America - Carolyn C Pike; Martin Williams; Andrea Brennan; Keith Woeste; James Jacobs; Sean Hoban; Melanie Moore; Jeanne Romero-Severson (Journal of Forestry, 2021)
Butternut is a relatively uncommon hardwood tree native to eastern North America. The species’ abundance has declined over the past 50 years, primarily because of an invasive pathogen (Ophiognomonia clavigignenti-juglandacearum [Oc-j]) and loss of suitable habitat for regeneration. Although genetic diversity of butternut is highest along the southern range edge, genetic diversity rangewide is fairly high, except in small and isolated populations. Although there is little evidence for even moderate resistance in native butternut, hybrids with Japanese walnut, a closely related species, display enough tolerance to infection to persist on the landscape and bear abundant nut crops year after year. Cryostorage of native embryogenic axes has yielded promising initial results as a strategy for gene conservation, but additional action is needed to conserve the remaining native gene pool. We describe a strategy for canker-resistance breeding in butternut using naturally occurring hybrids, hybrids in research orchards, and sources of native trees from as many regions as possible. Forest managers are encouraged to find surviving trees and collect seed for planting in suitable habitat to develop actionable knowledge that will enable the restoration of butternut with enough resistance to be self-sustaining on the landscape.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Nitrogen Demand Associated with Increased Biomass Yield of Switchgrass and Big Bluestem: Implications for Future Breeding Strategies - Michael D. Casler; DoKyoung Lee; Robert B. Mitchell; Paul R. Adler; R. Mark Sulc; Keith D. Johnson; Robert L. Kallenbach; Arvid R. Boe; Russell D. Mathison; Kim A. Cassida; Doohong Min; Kenneth J. Moore (BioEnergy Research, 2020)

A Method for Heterogeneous Spatio-Temporal Data Integration in Support of Marine Aquaculture Site Selection - Kate Beard; Melissa Kimble; Jing Yuan; Keith S. Evans; Wei Liu; Damian Brady; Stephen Moore (Journal of Marine Science and Engineering, 2020)
Aquaculture site selection, like most site suitability analyses, requires the assembly and combination of multiple variables. Geographic information systems GIS and multi-criteria evaluation (MCE) based approaches are commonly used for aquaculture site selection and demonstrate the integration of various information sources relevant for siting aquaculture. These analyses, however, tend to be one-time and result in a fixed site suitability plan. Within a dynamic marine environment experiencing potential regime shifts, a siting support tool that integrates new and evolving spatio-temporal data has benefits. This paper presents a flexible Voronoi cell-based GIS model for marine aquaculture siting. Rather than a one-time specification of suitable locations, the approach uses similarity measures on the characteristics of Voronoi cells to find cells with similar characteristics. We calculate a weighted aquaculture site tenure value for Voronoi cells that have been or are occupied by aquaculture farm sites. High scoring cells suggest suitable sites and serve as targets for similarity queries. We apply the approach to a case study on the coast of Maine using an R Shiny application to demonstrate the use of the framework for finding sites with similar characteristics.

Aerosol Deposition Impacts on Land and Ocean Carbon Cycles - Natalie M. Mahowald; Rachel Scanza; Janice Brahney; Christine L. Goodale; Peter G. Hess; J. Keith Moore; Jason Neff (Current Climate Change Reports, 2017)

Antibiotics as CECs: An Overview of the Hazards Posed by Antibiotics and Antibiotic Resistance - Geoffrey I. Scott; Dwayne E. Porter; R. Sean Norman; C. Hart Scott; Miguel I. Uyaguari-Diaz; Keith A. Maruya; Steve B. Weisberg; Michael H. Fulton; Ed F. Wirth; Janet Moore; Paul L. Pennington; Daniel Schlenk; et al. (Frontiers in Marine Science, 2016)

Strengthening confidence in climate change impact science - Mary I. O'Connor; Johnna M. Holding; Carrie V. Kappel; Carlos M. Duarte; Keith Brander; Christopher J. Brown; John F. Bruno; Lauren Buckley; Michael T. Burrows; Benjamin S. Halpern; Wolfgang Kiessling; Pippa Moore; et al. (Global Ecology and Biogeography, 2015)
Aim To assess confidence in conclusions about climate‐driven biological change through time, and identify approaches for strengthening confidence scientific conclusions about ecological impacts of climate change. Location Global. Methods We outlined a framework for strengthening confidence in inferences drawn from biological climate impact studies through the systematic integration of prior expectations, long‐term data and quantitative statistical procedures. We then developed a numerical confidence index ( C index ) and used it to evaluate current practices in 208 studies of marine climate impacts comprising 1735 biological time series. Results Confidence scores for inferred climate impacts varied widely from 1 to 16 (very low to high confidence). Approximately 35% of analyses were not associated with clearly stated prior expectations and 65% of analyses did not test putative non‐climate drivers of biological change. Among the highest‐scoring studies, 91% tested prior expectations, 86% formulated expectations for alternative drivers but only 63% statistically tested them. Higher confidence scores observed in studies that did not detect a change or tracked multiple species suggest publication bias favouring impact studies that are consistent with climate change. The number of time series showing climate impacts was a poor predictor of average confidence scores for a given group, reinforcing that vote‐counting methodology is not appropriate for determining overall confidence in inferences. Main conclusions Climate impacts research is expected to attribute biological change to climate change with measurable confidence. Studies with long‐term, high‐resolution data, appropriate statistics and tests of alternative drivers earn higher C index scores, suggesting these should be given greater weight in impact assessments. Together with our proposed framework, the results of our C index analysis indicate how the science of detecting and attributing biological impacts to climate change can be strengthened through the use of evidence‐based prior expectations and thorough statistical analyses, even when data are limited, maximizing the impact of the diverse and growing climate change ecology literature.

Erratum to: Agroforestry preferences in refugee hosting communities in Cameroon - Elizabeth A. Moore; John F. Munsell; A. L. Tom Hammett; Keith M. Moore (Agroforestry Systems, 2014)

Agroforestry preferences in refugee hosting communities in Cameroon - Elizabeth A. Moore; John F. Munsell; A. L. Tom Hammett; Keith M. Moore (Agroforestry Systems, 2014)

Safety and Efficacy of Flumazenil for Reversal of Iatrogenic Benzodiazepine-Associated Delirium Toxicity During Treatment of Alcohol Withdrawal, a Retrospective Review at One Center - Philip W. Moore; J Ward Donovan; Keith K. Burkhart; Jeffrey A. Waskin; Michelle A. Hieger; Audrey R. Adkins; Yijin Wert; David A. Haggerty; J. J. Rasimas (Journal of Medical Toxicology, 2014)

Quantitative approaches in climate change ecology - Christopher J. Brown; David S. Schoeman; William J. Sydeman; Keith Brander; Lauren B. Buckley; Michael Burrows; Carlos M. Duarte; Pippa J. Moore; John M. Pandolfi; Elvira Poloczanska; William Venables; Anthony J. Richardson (Global Change Biology, 2011)
Contemporary impacts of anthropogenic climate change on ecosystems are increasingly being recognized. Documenting the extent of these impacts requires quantitative tools for analyses of ecological observations to distinguish climate impacts in noisy data and to understand interactions between climate variability and other drivers of change. To assist the development of reliable statistical approaches, we review the marine climate change literature and provide suggestions for quantitative approaches in climate change ecology. We compiled 267 peer‐reviewed articles that examined relationships between climate change and marine ecological variables. Of the articles with time series data ( n = 186), 75% used statistics to test for a dependency of ecological variables on climate variables. We identified several common weaknesses in statistical approaches, including marginalizing other important non‐climate drivers of change, ignoring temporal and spatial autocorrelation, averaging across spatial patterns and not reporting key metrics. We provide a list of issues that need to be addressed to make inferences more defensible, including the consideration of (i) data limitations and the comparability of data sets; (ii) alternative mechanisms for change; (iii) appropriate response variables; (iv) a suitable model for the process under study; (v) temporal autocorrelation; (vi) spatial autocorrelation and patterns; and (vii) the reporting of rates of change. While the focus of our review was marine studies, these suggestions are equally applicable to terrestrial studies. Consideration of these suggestions will help advance global knowledge of climate impacts and understanding of the processes driving ecological change.

Functional MRI of Language in Aphasia: A Review of the Literature and the Methodological Challenges - Bruce Crosson; Keith McGregor; Kaundinya S. Gopinath; Tim W. Conway; Michelle Benjamin; Yu-Ling Chang; Anna Bacon Moore; Anastasia M. Raymer; Richard W. Briggs; Megan G. Sherod; Christina E. Wierenga; Keith D. White (Neuropsychology Review, 2007)

Construction of a Festuca pratensis BAC library for map-based cloning in Festulolium substitution lines - Iain S. Donnison; Donal M. O’Sullivan; Ann Thomas; Peter Canter; Beverley Moore; Ian Armstead; Howard Thomas; Keith J. Edwards; Ian P. King (Theoretical and Applied Genetics, 2005)

Contributions from the combined 7th International Conference on Gas in Marine Sediments and the NATO Advanced Research Workshop on Seafloor Hydrocarbon Seeps, Geology Institute, Azerbaijan Academy of Sciences, Baku, 7?11 October 2002 - John M. Woodside; Robert E. Garrison; J. Casey Moore; Keith A. Kvenvolden (Geo-Marine Letters, 2003)

The Impact that Elevation Has on the ENSO Signal in Precipitation Records from the Gulf of Alaska Region - G. W. K. Moore; Keith Alverson; Gerald Holdsworth (Climatic Change, 2003)

Human TE671 cells express functional motilin receptors - Lubing Zhou; Joseph W. Gunnet; Mike Moore; Ellen V. Cryan; Jun Z. Xu; Keith T. Demarest (Biotechnology Letters, 2001)

Marine Biogeochemical Modeling: Recent Advances and Future Challenges - Scott Doney; Iva Lima; Keith Lindsay; Keith Moore; Stephanie Dutkiewicz; Marjorie Friedrichs; Richard Matear (Oceanography, 2001)

Putting Together the Big Picture: Remote-Sensing Observations of Ocean Color - James Yoder; Keith Moore; Robert Swift (Oceanography, 2001)

Isolation and Identification of Ruminal Methanogens from Grazing Cattle - Graeme N. Jarvis; Carsten Strömpl; Diana M. Burgess; Lucy C. Skillman; Edward R. B. Moore; Keith N. Joblin (Current Microbiology, 2000)